National strategy for open access to scientific publications and research data in Slovenia 2015–2020 / Nacionalna strategija odprtega dostopa do znanstvenih objav in raziskovalnih podatkov v Sloveniji 2015–2020 - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
At the beginning of the 21st century, modernization of scientific communication has increasingly become a necessity. So far, there is only limited access to research data. The European Commission therefore started to introduce changes in the field of scientific communication in 2004. The program, Horizon 2020, provides open access to all peer-reviewed and publicly funded publications within European Union (EU) countries (MedOANet, RECODE, PASTEEUR 4OA projects) (1–4).